Rainy Days / Short Stories by Contemporary Spanish Women Writers = Dias de Lluvia. - Lunati, Montserrat (Aris & Phillips Hispanic classics., 2018)
This anthology collects sixteen stories by contemporary Spanish women writers: Pilar Cibreiro, Cristina Fernández Cubas, Paloma Díaz-Mas, Adelaida García Morales, Lourdes Ortiz, Laura Freixas, Marina Mayoral, Mercedes Abad, Rosa Montero, Maruja Torres, Soledad Puértolas, María Eugenia Salaverri, Nuria Amat, Juana Salabert, Luisa Castro and Berta Marsé. The stories are in the original Spanish and with facing-page English translations, and comprehensive bio-bibliographical information on each author is also included in the volume.